Nanoparticles' Promises and Risks : Characterization, Manipulation, and Potential Hazards to Humanity and the Environment - Lungu, Mihai; Neculae, Adrian; Bunoiu, Madalin; Biris, Claudiu (Springer International Publishing : Imprint: Springer, 2015)
The focus of this interdisciplinary volume is on four areas of nanoparticle research: characterization, manipulation, and potential effects on humanity and the environment. The book includes a comprehensive collection of data on industrial nanoparticle creation and the characterization of the nanoscale products of these processes. The authors describe the effects of these nanoscale structures on human health and discuss prospective implementations for detection and characterization of nanoparticles in the environment. They recommend, utilizing the most up-to-date understanding of nanotechnology, methods for limiting the negative effects of these products on the environment and human health through manipulation, sorting, and filtration.